Los Derechos Humanos en el Código de Derecho Canónico - José María Díaz Moreno, S. J. (Miscelánea Comillas, 2009)
After some short indications about the attitude of the Catholic Church before the various declarations of the Human Rights, the doctrine, before andafter the Second Vatican Council, on the same, the first attempt to set up the norms of the rights of the baptized and its promulgation in the current Canon Law Code, a comparison is made between some of Human Rights established in the Universal Declaration of 1948 and certain canons related to the same.